1995
DOI: 10.1007/bf01276511
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamethoxazole-trimethoprim double-blind, placebo-controlled, crossover trial in Machado-Joseph disease: sulfamethoxazole-trimethoprim increases cerebrospinal fluid level of biopterin

Abstract: We performed a double-blind, placebo-controlled, crossover trial of sulfamethoxazole-trimethoprim (S-T) in 8 patients with Machado-Joseph disease (MJD), and measured the blood and cerebrospinal fluid levels of biopterins, biogenic amines or metabolites, and folate. The clinical results were as follows; mild improvements of hyperreflexia of knee jerks and of rigospasticity of the legs during S-T treatment period. In addition, S-T significantly reduced the times of 8 motor activities on the timed tests. The bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…No differences were noted in sub-group analysis according to age, sex, duration of illness, phenotype, age at onset, or number of CAG triplets (141). These categorical results contrast with the more favourable outcomes obtained in a study that included eight patients with MJD (142), and with three other reports of individual patients (143)(144)(145) that received TS. The reason for the differing results could lie in the absence of molecular diagnosis in the latter studies, or in other methodological differences (141).…”
Section: Degenerations Of the Dentate Nucleus And Efferent Tracts Of contrasting
confidence: 54%
“…No differences were noted in sub-group analysis according to age, sex, duration of illness, phenotype, age at onset, or number of CAG triplets (141). These categorical results contrast with the more favourable outcomes obtained in a study that included eight patients with MJD (142), and with three other reports of individual patients (143)(144)(145) that received TS. The reason for the differing results could lie in the absence of molecular diagnosis in the latter studies, or in other methodological differences (141).…”
Section: Degenerations Of the Dentate Nucleus And Efferent Tracts Of contrasting
confidence: 54%
“…[140] First RCT in SCA3/MJD [67,68] RNAi silencing of mutated ataxin-3 in transgenic rodent [116] Large natural history studies are published [33,34] magnitude of effect that should be pursuited in future RCT [41]. For detailed information regarding validation, psychometric properties, NH and utilization of SCA scales, we suggest a recent systematic review [45].…”
Section: Sleep Disorders Expert Opinionmentioning
confidence: 98%
“…Two studies evaluated sulfamethoxazole-trimethoprim (SMT + TMP) [67,68] and concluded that the drug was effective in SCA3/MJD due to improvements on clinical parameters after 4 weeks of treatment. These studies illustrate well some of the problems that researchers faced when trying to find an effective treatment for the recently discovered disorder.…”
Section: Treatmentmentioning
confidence: 99%
“…There was a modest improvement of undetermined clinical relevance [88]. Sakai et al (1995) used a very similar design and also found a small improvement which the authors attributed to an increase of brain biopterins caused by the treatment [89]. These effects were not confirmed in a 26 week, double-blind, placebo-controlled crossover trial in 22 SCA3 patients [90].…”
Section: Previous Clinical Trials In Sca2 and Sca3 Patientsmentioning
confidence: 99%